Kinetic-Spectrophotometric Method for Diclofenac Quantification - Monzón, Celina María (2012)
This paper introduces a kinetic-spectrophotometric method for diclofenac quantification and its application to pharmaceutical preparations. The redox reaction rate between diclofenac and KMnO4 in a strong acidic environment is determined. Plotting initial slope vs. concentration a good linearity has been found. Linear range of the essay was 5-20 ppm. The effect of temperature on the reaction rate has been studied and Ea was 21.48 kJ/mol. The proposed method was found to be highly precise, having a relative standard deviation, CV% = 1.3% for repeatability (n=10). Recovery of analyte in placebo 98.7 - 108.15%, values that fall within the requirements set by USP and ANMAT (National Drug, Food and Medical Technology Administration of Argentina). This spectrophotometric method was compared with HPLC. Statistical data show no significant difference between them. The proposed method was found to be simple, rapid, specific, allowing the determination without preliminary extraction procedures.